Efektivitas LAPSPI Dalam Penyelesaian Sengketa Layanan Digital Banking Di Indonesia - Dwi Cahya Maulani; Ria Febriani; Puput Puspita Sari; Neli Aida; Muhammad Mufti Hudani; Qurrota Ayu Nindien (Jurnal Ekonomi dan Bisnis Digital, 2025)
The Indonesian Banking Dispute Resolution Alternative Institution (LAPSPI) holds a vital role in addressing digital banking disputes amid the rapid growth of the financial sector. Based on a qualitative descriptive study through literature review, mediation emerges as the most effective approach for resolving technical and service-related issues, while digital security disputes often require legal intervention. One major challenge is the low public awareness of LAPSPI's functions and mechanisms. Despite this, LAPSPI proves to be an efficient, fair, and adaptable non-litigation forum for resolving conflicts outside the court system. Its presence supports consumer protection and strengthens trust in digital financial services, making it a crucial element in Indonesia’s effort to modernize and secure its banking industry in the digital era.